Hematological Findings and Alteration of Oxidative Stress Markers in Hospitalized Patients with SARS-COV-2 - GJorgjievska, Kalina; Petrushevska, Marija; Zendelovska, Dragica; Atanasovska, Emilija; Spasovska, Katerina; Stevanovikj, Milena; Grozdanovski, Krsto (Macedonian Academy of Sciences and Arts/Walter de Gruyter GmbH, 2022)
Background/aim: Hematological parameters are the starting point in COVID-19 severity classification. The aim of this study was to analyze oxidative stress in hospitalized COVID-19 patients and to determine its association with D-dimer, neutrophil to lymphocyte ratio (NLR), and platelets to lymphocyte ratio (PLR) as markers for disease progression. Materials and methods: 52 patients with moderate and severe forms of COVID-19 were enrolled. A hematological and coagulation profile was performed for each patient. PAT (total antioxidant power, iron-reducing) and d-ROMs (plasma peroxides) were determined in serum at admission and 7 days after hospitalization. Results: The severe group presented parameters that indicated a poor prognosis. Patients that recovered had a significant reduction in d-ROM (t-test, p<0.01) and improvement in oxidative stress index (t-test, p<0.05). Patients that died had significantly decreased PAT (p<0.01) resulting in an increase in oxidative stress. Except for d-ROM vs PLR in both groups and d-ROM vs D-dimer in the severe group, a good correlation between oxidative stress parameters and D-dimer, PLR, and NLR was demonstrated (p<0.01). Conclusion: Our results show that oxidative stress markers can be used as a tool for disease progression in COVID-19. This analysis is easily accessible and affordable in addition to conventional hematological parameters performed for severity classification.
Keywords: COVID-19; oxidative stress; D-dimer; neutrophil to lymphocyte ratio; platelets to lymphocyte ratio